R. K. Narayan, the Novelist of the Commoners and His Ironic Sense of Humour - Priydarshi, Ashok Kumar (Journal of Advanced Research in English & Education; Vol 5 No 2 (2020): Journal of Advanced Research in English and Education, 2021)
Narayan’s humour is direct course of his intellectual analysis of the contradictions in human experience tragically or comically. Irony can be tragic also, but in Narayan our concern is only the irony, that works as a base for Narayan’s humour the instances of which are found at every step in his novels. The keynote of Narayan’s interest is his very minute observation and subtle ironic harmonious way of telling his story. There is, in his novels, scarcely audible laughter shot through all the novels. His comic vision is ironical. His all embracing irony, which includes the particular social context in his men and women, who have their various transactions and the existential reality based on their particular experiences. The clash between the tradition and modernity in which Narayan’s characters are sandwiched has ironical implications. Narayan’s comprehensive knowledge of the perception of inherent irony in human life makes him a master of comedy, who is nor unware of the tragedy of human situation and tragi-comedies of mischance and misdirection. The basic comic situation in Narayan’s novels is one of the derivation from the normal and in the plots of his novels, he follows the usual pattern of irony order, disorder, order. His irony is free from the satiric spirit of condemnation and censure. His ironic vision is closer in spirit to Chaucer, Shakespear and Dickens. His closeness to Chekhov is striking the same objectivity, the same freedom from comment, the same intricate alliance of humour with tragedy the comic irony with, as Greene puts it and the same seeming indirection even with which the characters, on the last page, appear to vanish into life. How to cite this article:  Priydarshi AK. R. K. Narayan, the Novelist of the Commoners and His Ironic Sense of Humour. J Adv Res Eng & Edu 2020; 5(2): 11-12. DOI: https://doi.org/10.24321/2456.4370.202007